Subregional Timber Supply Projections with Chip-n-Saw Stumpage: Implications for Southern Stumpage Markets. Issue 6 (17th June 2019) - Parajuli, Rajan; Tanger, Shaun; Abt, Robert; Cubbage, Fred
Abstract: Softwood chip-n-saw (CNS), an intermediate stumpage product between sawtimber and pulpwood, has become a mainstay in southern timber markets in recent years. Most of the previous studies in southern timber markets primarily focused on pulpwood and sawtimber markets, and often overlooked CNS as a standalone timber product. Using the Subregional Timber Supply model, this study examines the dynamics of sawtimber- and pulpwood-dominated softwood stumpage markets with growing CNS markets in the US South. Results suggest that South-wide CNS inventory increases over the short run but begins to decrease by 2024, which leads to CNS prices rising over the years. The projected trends vary widely from one wood basket to another. This study provides additional nuance to future prospects of southern timber markets.